Detection and molecular characterization of chicken infectious anaemia virus in poultry flocks in Haryana - BRAR, RAHUL; BAHNOT, VANDNA; MAHAJAN, N K; TOMAR, PIYUSH; PRAKASH, ANAND; MAAN, SUSHILA (The Indian Journal of Animal Sciences, 2020)
Chicken infectious anaemia virus (CIAV) is an economically important pathogen affecting poultry industry worldwide. Commercial poultry flocks (26) suspected to be affected with chicken infectious anaemia (CIA) were processed for Polymerase Chain Reaction (PCR) using VP2 gene primers and characterized by partial gene sequencing. The PCR revealed 26.9% (7/26) poultry flocks positive for CIAV. Eleven PCR products of CIAV DNA were sequenced. The partial nucleotide sequence analysis of VP2 genes revealed that 11 field strains had 99.2 to 100% similarity among themselves and with the Indian strains. The VP2 gene sequences of 11 field strains showed 97.5 to 100% similarity to the field strains sequences reported from all over the world. On the basis of partial nucleotide sequencing analysis of VP2 gene, our findings suggest that the viral strains circulating in Haryana have similarity to other Indian strains.